Analysing the effects of tax-benefit reforms on income distribution: A decomposition approach - Olivier Bargain; Tim Callan (University College Dublin, UCD School of Economics, 2007)
To assess the impact of tax-benefit policy changes on income distribution over time, we suggest a methodology based on counterfactual simulations. We start by decomposing changes in inequality/poverty indices into three contributions: reforms of the tax-benefit structure (rules, rates, etc.), changes in nominal levels of market incomes and tax-benefit parameters (benefit amounts, tax bands, etc.), and all other changes in the underlying population (market income inequality, demographic composition, employment level, etc.). Then, the decomposition helps to extract an absolute measure of the impact of tax-benefit changes on inequality when evaluated against a distributionally-neutral benchmark, i.e. a situation where tax-benefit parameters are adjusted in line with income growth. We apply this measure to assess recent policy changes in twelve European countries. Finally, the full decomposition allows quantifying the relative role of policy changes compared to all other factors. We provide an illustration on France and Ireland and check the sensitivity of the results to the decomposition order.
Keywords: H23; H53; I32; 330; tax-benefit policy; inequality; poverty; decomposition; microsimulation; Steuerreform; Einkommensverteilung; Verteilungsgerechtigkeit; Armut; Soziale Lage; Dekompositionsverfahren; Schätzung; Europa